Bivalvos perforadores de esqueletos de corales escleractiniarios en la Isla de Gorgona, Pacífico Colombiano - Cantera-K., Jaime Ricardo (1988)
This paper presents systematic and ecological remarks about three species of Mytilidae (Lithophaga aristata, L. plumula, and L. hancocki) and one of Gastrochaenidae (Gastrochaena ovata) found boring scleractinian corals of Gorgona lsland; Colombian Pacific coast. It includes a description of diagnostic characteristics of the shells, notes about habitat, bathymetríc range, sizes and geographical distribution. The dead bases of branched corals, and live parts of massive species, present more taxa and numbers of borers.